ANALISIS PENGARUH BREAKWATER TERHADAP TRANSPOR SEDIMEN PANTAI SINDULANG 1 SAMPAI TUMUMPA 2 - Manansang, Merry Kristin; Hendratta, Liany A.; Dundu, Ariestides K. T. (JURNAL SIPIL STATIK, 2018)
Utilization of Littoral develops continuously along with economic developments and technological advancements nowadays. Therefore, special attention is needed to overcome the problems that may arise in Littoral including coastal areas. One of the most popular beach problems for this time is the unbalanced sediment transport causing Coastal Erosion. The retreat of shorelines is generally due to coastal processes such as erosion and abrasion that will harm either the local population or life sustainability.From Sindulang Beach until Tumumpa II region where is located on Boulevard II experiencing erosion and abrasion. This certainly cannot be ignored for long because besides it will be able to damage the facilities and infrastructure of society and other public infrastructure but it also can harm the lives of coastal communities.Through this paper, The Author tries to do new thing by placing breakwater as a building that has an influence on sediment transport. We know usually The Breakwater is a Shore protector for the wave attacks, this time we try to see its effect on the sediment transport. Through this study, The Author conducts the modeling of coastline with four variations of breakwater. First Variation: The breakwater is placed in parallel against the west-east direction separately, Second Variation: the breakwater is placed in parallel against the shoreline separately but it is longer than the First Variation, Third Variation: the breakwater is placed in parallel against coastline with tightly placed and longer than First Variation, Fourth Variation: breakwater is placed in parallel against the coastline with very tightly placed and longer than First Variation. The Differences in length of breakwater causes the difference of sediment transported too. In the First Variation, sediment is transported up to 12370 m3 to the right, Second Variation; sediment is transported up to 17589 m3 to the right, Third Variation; sediment is transported up to 22682 m3 to the right, Fourth Variation; sediment is transported up to 11478 m3 to the right. Then we found the configuration of the Second Variation of breakwater beach building is most efficient. The calculation of the effect of groins on shoreline is done with Genesis Software. Before using Genesis for modeling, the Genesis should be calibrated to the calibration parameters K1, K2 and d50 afterward doa Sensitivity Test. After the Test, take the value that produces the smallest DYrms among The values of K1, K2 and d50. The values of K1, K2 and d50 are 0.11, 0.2 and 0.5 mm. The data that must include in the genesis are wave data, initial and measured coastline, offshore depth and depth of cover. Wave data is obtained from wind data analyzed by SMB method. The wave data that include in Genesis are the period, height and direction of the wave where the wave height that include in this case is the average wave height. Keywords: Breakwater, Sediment Transport, Sindulang-Tumumpa Beach 2.